Pengaruh Kompetensi Mediator dan Biaya Penyelesaian Sengketa terhadap Efektivitas Alternative Dispute Resolution - Ramaji Themas; Asep Suherman (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of mediator competence and dispute resolution costs on the effectiveness of Alternative Dispute Resolution (ADR) as one of the non-litigation mechanisms in the Indonesian legal system. The competence of the mediator is seen as an important factor because it reflects the expertise, communication skills, and ability to maintain neutrality in facilitating the agreement of the parties. Meanwhile, the cost of dispute resolution is a significant consideration for the public in choosing ADR over litigation which is often time-consuming and expensive. The research method used is a quantitative approach with data collection through questionnaires that are distributed to respondents who have experience in the ADR process. Data analysis was carried out using multiple regression to determine the magnitude of the influence of each independent variable on the bound variable. The results show that both the competence of the mediator and the cost of dispute resolution have a significant positive influence on the effectiveness of ADR, so both need to be considered to improve the quality of non-litigation dispute resolution in Indonesia.